Energy Balance of Laying Hens under Different Climates - Jalaludin, S.; Tham, S. K.; Sykes, A. H. (1979)
A series of short term (3-4 weeks) energy balance experiments on laying hens were carried out under temperate and tropical climates. The results indicated that hens on ME restriction could produce egg while at the same time maintained positive energy balance. This was possible because nutrient requirements to maintain higher body weight which resulted from energy restriction, could have been reduced. Total heat production data obtained for temperate and tropical climates were 172 and 187 kcal(kgo.75 respectively.